Hassan Al Faiz Mohamed awarded Mercedes-Benz scholarship - UMP, PNC (2019)
Universiti Malaysia Pahang (UMP) undergraduate from the Faculty of Mechanical Engineering & Manufacturing (FKMP), Hassan Al Faiz Mohamed Ahmed Hafez – who is undergoing the dual-degree programme coordinated by UMP and HsKA University of Applied Sciences of Germany, for a Bachelor’s Degree (Honors) in Automotive Engineering – lucked out when he was selected to be the recipient of the Mercedes-Benz (Malaysia) Sdn Bhd (MBM) scholarship for the duration of his baccalaureate.